Pore Structure Characteristics and Its Effect on Mechanical Performance of Cemented Paste Backfill - Huan, Chao; Zhu, Chao; Liu, Lang; Wang, Mei; Zhao, Yujiao; Zhang, Bo; Zhang, Xiaoyan (Frontiers in Materials, 2021)
As a kind of porous material, the pore characteristics of cemented paste backfill (CPB) is strongly correlated to its mechanical properties. In this study, CPB specimens were prepared with tailings/cement ratio (T/C ratio) of 4, 6, and 10, and cured for 3, 7, 14, 28 days. Pore structures characteristics of CPB specimens were analysed using nuclear magnetic resonance (NMR) and scanning electronic microscopy (SEM). The uniaxial compressive strength (UCS) was used to describe the mechanical property of CPB specimens. The effect of T/C ratio and curing time on the pore characteristics of CPB specimens and the effect of pore structure changes on the UCS was investigated. The results indicated that: (i) the integrity of CPB microstructure was closely related to the development status of the pore structure, which can be represented by micro-parameters like porosity, average pore area, et al. The more integrate CPB microstructure was, the higher the UCS was; (ii) with the same curing time and different T/C ratio, the pore size was mainly between 10 and 100 nm, and a “λ” shape distribution was observed. As the curing time increased, the maximum of the “λ” distribution shifted left, meaning that the size of pores in CPB decreased; (iii) At the same curing time, the pores size of less than 10 nm gradually decreased with a higher T/C ratio while those with size of 10-100 nm and ＞1000nm gradually increased. and (iv) the extension of small pores lead to the cross-connection of pores and resulted in the fracture of CPB, which was shown as a crack on the main section. This work analysed the heterogeneity of CPB in detail, and can provide a basis for studying the constitutive relations of CPB.